Bipolar TURP in high-risk patients with large prostate gland: our experience - Wani, Prince M.; Wani, Mohammad S.; Bhat, Arif H.; Khawaja, Abdul R.; Malik, Sajad A.; Das, Yaser A.; Para, Sajad A.; Dar, Manzoor A. (International Surgery Journal, 2021)
Background: The present gold standard monopolar-TURP is associated with a number of complications and has less safety margin in comorbid patients. Bipolar TURP is a modification of conventional M-TURP and has the potential to overcome its most prominent shortcomings with better safety profile in patients with comorbidities. Aim of the study was to evaluate the efficacy of bipolar-TURP in terms of operative and postoperative parameters. Methods: This prospective study was conducted in the department of urology SKIMS Srinagar, from April-2019 to October 2020. Forty-five patients with one or more comorbidities and BHP, with a prostate weight ≥60 gm was evaluated. Operative and postoperative parameters were recorded and patients followed with IPSS and uroflowmetry for a period of 6-months. Results: Of 45 patients who underwent B-TURP, pre-operative parameters were mean age(years) 66.59±9.88, mean prostate size (gm) 77.42±18.4, mean IPSS of 26.3±2.9, mean serum PSA (ng/dl) of 2.32±0.88, mean Qmax (ml/s)of 7.71±2.41 and PVRU of 113.45±16.5 ml. Operative and post-operative parameters were, mean operative time(min) of 68.14±29.6, TUR syndrome in none, mean change in Na+ of -0.98±0.75 meq/l, mean change in Hb of -1.66±0.68 g/dL, mean irrigation time (hours) 24.53±5.46, clot retention in 3 (6.66%) patients, transfusion in 2 (4.44%) patients, mean postoperative catheter time(hours) 69.5±10.5 and mean hospital stay 3.6±1.61 days. Two (4.44%) patients developed stricture urethra and were managed with urethral dilatation. IPSS and Qmax at 6-weeks were 10.2±2.18 and 16.22±2.31 ml and at 6-months were 6.43±1.16 and 19.12±3.14 ml respectively. Conclusions: B-TURP seems to be a more sensible choice for patients with underlying comorbidities or implanted cardiac devices.